2023
DOI: 10.1002/smll.202301955
|View full text |Cite
|
Sign up to set email alerts
|

Deterministic Magnetic Switching in Perpendicular Magnetic Trilayers Through Sunlight‐Induced Photoelectron Injection

Abstract: Finding an energy‐efficient way of switching magnetization is crucial in spintronic devices, such as memories. Usually, spins are manipulated by spin‐polarized currents or voltages in various ferromagnetic heterostructures; however, their energy consumption is relatively large. Here, a sunlight control of perpendicular magnetic anisotropy (PMA) in Pt (0.8 nm)/Co (0.65 nm)/Pt (2.5 nm)/PN Si heterojunction in an energy‐efficient manner is proposed. The coercive field (HC) is altered from 261 to 95 Oe (64% variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…According to the reported works, changes in the magnetic anisotropy and magnetization in the ferromagnetic layer originating from photoinduced electron doping can be quantified by in situ measurements of ESR and VSM. [35][36][37][38] The M-H loops of Co 60 Al 40 (2 nm)/PTB7-Th:PC 71 BM/Pt are illustrated in Figure 3a, where a decrease of 13.4% of M s in Co 60 Al 40 is obtained under sunlight irradiation. Figure 3b shows a zoom-in view around the coercive field (H c ), which drops from 24 to 20 Oe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the reported works, changes in the magnetic anisotropy and magnetization in the ferromagnetic layer originating from photoinduced electron doping can be quantified by in situ measurements of ESR and VSM. [35][36][37][38] The M-H loops of Co 60 Al 40 (2 nm)/PTB7-Th:PC 71 BM/Pt are illustrated in Figure 3a, where a decrease of 13.4% of M s in Co 60 Al 40 is obtained under sunlight irradiation. Figure 3b shows a zoom-in view around the coercive field (H c ), which drops from 24 to 20 Oe.…”
Section: Resultsmentioning
confidence: 99%
“…This results from band filling of Co film by photovoltaic electrons doping, leading to the depressed M s and H c accordingly, which has been discussed comprehensively in our previous works. [37,38] Figure 3ch shows the FMR spectra obtained by a test with a step of 1°. We conducted the in situ photovoltaic process on the Co 60 Al 40 film, and variations of FMR spectra can be observed by ESR under different light intensities, which is illustrated in Figure S6 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These experimental results demonstrated the ability of visible light to control magnetization reversal in synthetic antiferromagnets and provide an important basis for the development of future spintronic memory and logic devices. Another heterostructure Pt/Co/Pt/PN Si was tested to verify the magnetization flip under sunlight irradiation by Zhao et al 214 They found a decreasing trend in the coercivity field under sunlight irradiation, making a deterministic magnetization flip of almost 180°possible. In addition, a nonvolatile magnetization flip was achieved by alternating sunlight and magnetic field bias, as shown in Figure 11f.…”
Section: Sunlight Modulation Of Magnetismmentioning
confidence: 99%
“…Deterministic magnetization strength switching process, change of I – V magnetic state, and periodic magnetization strength switching in the Pt/Co/Pt/PN Si heterostructure under bias field-assisted and sunlight control. Reprinted with permission from ref . Copyright 2023, Wiley-VCH GmbH.…”
Section: Development Of Optical Controllable Magnetism Devicesmentioning
confidence: 99%